Infectious diseases in Tachypleus gigas during captive breeding and rearing - John, Akbar; Sheikh, Hassan I.; Yunus, Kamaruzzaman (2019)
Captive breeding and rearing of horseshoe crab is a promising step towards its conservation and sea-ranching. However, infectious and non-infectious diseases are the main challenges in determining the health condition of horseshoe crabs under captivity. Both developing eggs as adult horseshoe crabs are susceptible to various pathogens such as protozoa, bacteria, fungi, algae and other micro and meiobenthos. We address a number of pathogens that caused mortality in captive adult and juvenile horseshoe crabs. Samples were taken from gill fluids, gill tissue, and eggs of captive T. gigas. The microbes were cultured in various media (Tryptic Soy agar, Muller-Hinton agar and Nutrient agar) at different culture conditions (25 ºC for 4 days or 37 ºC for 24 hrs) with and without salt (1% NaCl) to facilitate the growth and viability of wide range of microbes. Genomic DNA extraction, PCR amplification and DNA sequencing were carried out to target molecular identification of the pathogens using partial sequencing of 16S rRNA gene for bacteria and ITS gene for fungi. Aeromonas caviae strains were isolated from the gill fluid of an infected animal that died within a day of exposure. Lysinibacillus fusiformis strains were isolated from gill tissues of animals kept under prolonged captivity (>6 months). Aspergillus aculeatus strains were screened from eggs reared in captivity where development was retarded or ceased post infection. The diverse, frequency and varying targets of these microbial infections requires more studies on the culture condition, feeding and other parameters used for maintaining horseshoe crabs in laboratory settings.